2015
DOI: 10.1521/ijct.2015.8.2.143
|View full text |Cite
|
Sign up to set email alerts
|

Guilt as a Mediator of the Relationship Between Depression and Posttraumatic Stress With Suicide Ideation in Two Samples of Military Personnel and Veterans

Abstract: Depression, posttraumatic stress (PTS), and guilt have been implicated as risk factors for suicide ideation (SI) among military personnel and veterans. Conceptual and empirical work suggests that guilt may mediate the relationship of depression and PTS with SI. The current study explored this hypothesis in two cross-sectional samples of military personnel and veterans (n = 464 and n = 158). Path analyses showed good fit for both samples [Sample 1: χ 2 (1) = 2.18, p = .140; CFI = 1.00; RMSEA = .05; WRMR = .23; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 38 publications
4
22
0
Order By: Relevance
“…These findings are similar to Bryan et al. 's () study, which found that overall guilt mediated the relationship between symptoms of PTSD and depression and SI.…”
Section: Discussionsupporting
confidence: 90%
“…These findings are similar to Bryan et al. 's () study, which found that overall guilt mediated the relationship between symptoms of PTSD and depression and SI.…”
Section: Discussionsupporting
confidence: 90%
“…Negative self-concept, in particular, appears to be especially key to understanding the emergence of suicidal thoughts and behaviors within the context of PTSD. Guilt, remorse, self-blame, and self-criticism not only increase risk of suicidal thoughts and behaviors [20][21][22][23][24]; accumulating evidence suggests they explain the relationship of PTSD with suicide-related outcomes [22,25,26]. Guilt has also been found to be a risk factor for the later development of other trauma-related sequelae such as depression and substance use disorders [27][28][29][30][31], each of which serves as a suicide risk factor in its own right.…”
Section: Conceptualizing Suicidal Behaviormentioning
confidence: 99%
“…Initial evidence supports this hypothesis. Results from Bryan et al (2013) suggested that guilt and shame together mediated the relationship between PTSD and SI, and further research showed that guilt partially mediated the relationship between PTSD and SI (Bryan et al, 2015). A recent study of Iraq and Afghanistan veterans also showed that trauma-related guilt mediated the relationship between PTSD symptoms and SI (Tripp & McDevitt-Murphy, 2016).…”
Section: Introductionmentioning
confidence: 99%